“Metropolitan Parks” in Southern Barcelona: Key Nodes at the Intersection of Green Infrastructure and the Polycentric Urban Structure - Joan Florit-Femenias; Carles Crosas; Aleix Saura-Vallverdú (Land, 2025)
Contemporary urban planning faces the ongoing challenge of developing Green Infrastructure capable of providing vital ecosystem services. Within this framework, the Barcelona metropolitan area has advanced a network of parks that, while serving local neighborhoods, also aim for metropolitan relevance. This study offers a forward-looking analysis of selected parks in the southern Llobregat River basin—an area shaped by historic villages and working-class settlements—to evaluate their contribution to both Green Infrastructure and the region’s polycentric structure. Building on previous landmark studies and multidisciplinary perspectives, the research examines eight parks through four spatial and scalar lenses, assessing their territorial role and accessibility, ecological connectivity, urban integration and permeability, and landscape design with both qualitative and quantitative data. Using a comparative framework alongside research-by-design methods tested in urban design studios, the research links analytical insights to design-based strategies. The outcome is a set of actionable guidelines aimed at enhancing local park performance, with broader implications for over 50 ‘Metropolitan Parks’ spread in more than 30 municipalities. These insights contribute to shaping a more integrated, livable, and resilient metropolitan region.